Ultra-Fine Bubble Distributions in a Plant Factory Observed by Transmission Electron Microscope with a Freeze-Fracture Replica Technique - Uchida, Tsutomu (Nanomaterials (Basel), 2018)
Water containing ultra-fine bubbles (UFB) may promote plant growth. But, as UFBs are too small to distinguish from other impurities in a nutrient solution, it is not known if UFBs survive transport from the water source to the rhizosphere. Here we use the freeze-fracture replica method and a transmission electron microscope (TEM) to observe UFBs in the nutrient solutions used in a crop-growing system known as a plant factory. In this factory, TEM images taken from various points in the supply line indicate that the concentration of UFBs in the nutrient solution is conserved, starting from their addition to the nutrient solution in the buffer tank, through the peat-moss layer, all the way to the rhizosphere. Measurements also show that a thin film formed on the surface of UFBs in the nutrient solution, with greater film thickness at the rhizosphere. This film is considered to be made from the accumulation of impurities coming from solute and the peat-moss layer.